STUDIES OF MALARIA TRANSMISSION RISK FACTORS IN A TIME OF MILITARY-POLITICAL CRISIS IN BOUAKE URBAN AREA (IVORY COAST) - Adja, Akre Maurice; Yobo, Mabot Celine (European Scientific Journal, ESJ, 2015)
In order to assess the risk of malaria transmission to which populations are exposed in a time of war in besieged areas, studies were conducted between April and June, 2008, in a district of Bouaké, a town in the humid savannah of the central Ivory Coast. This study’s objective was to describe the malaria situation in an urban environment during a period of military crisis. Data were gathered from personal interviews with heads of households and direct observations. Analysis of our results has made it possible to assess the various sources of mosquito proliferation, especially anopheles malaria vectors. The presence of anopheles is associated with two factors: kennedy’s natural environment; and the deterioration of the surroundings caused by war. Indeed, the principal breeding sites encountered in kennedy are mainly comprised of vegetable and rice plots in the low land; puddles of water in the cracks resulting from damaged roads; and ruined or abandoned dwellings. The wide array of anopheles breeding sites and the deterioration of the environment are all factors which increase the risk of malaria transmission in Kennedy, where most inhabitants do not protect themselves against mosquito bites.